Cortical Modulation of Motor Control Biofeedback among the Elderly with High Fall Risk during a Posture Perturbation Task with Augmented Reality - Chang, Chun-Ju; Yang, Tsui-Fen; Yang, Sai-Wei; Chern, Jen-Suh (Frontiers in Aging Neuroscience, 2016)
The cerebral cortex provides sensorimotor integration and coordination during motor control of daily functional activities. Power spectrum density (PSD) based on electroencephalography (EEG) has been employed as an approach that allows an investigation of the spatial-temporal characteristics of neuromuscular modulation; however, the biofeedback mechanism associated with cortical activation during motor control remains unclear among elderly individuals. Thirty one community-dwelling elderly participants were divided into low fall-risk potential (LF) and high fall-risk potential (HF) groups based upon the results obtained from a receiver operating characteristic analysis of the ellipse area of the center of pressure. EEG was performed while the participants stood on a 6-degree-of-freedom Stewart platform, which generated continuous perturbations and done either with or without the virtual reality scene. The present study showed that when there was visual stimulation and poor somatosensory coordination, a higher level of cortical response was activated in order to keep postural balance. The elderly participants in the LF group demonstrated a significant and strong correlation between postural-related cortical regions; however, the elderly individuals in the HF group did not show such a relationship. Moreover, we were able to clarify the roles of various brainwave bands functioning in motor control. Specifically, the gamma and beta bands in the parietal–occipital region facilitate the high-level cortical modulation and sensorimotor integration, whereas the theta band in the frontal–central region is responsible for mediating error detection during perceptual motor tasks. Finally, the alpha band is associated with processing visual challenges in the occipital lobe. With a variety of motor control demands, increment in brainwave band coordination is required to maintain postural stability. These investigations shed light on the cortical modulation of motor control among elderly participants with varying fall-risk potentials. The results suggest that, although elderly adults may be without neurological deficits, inefficient central modulation during challenging postural conditions could be an internal factor that contributes to the risk of fall. Furthermore, training that helps to improve coordinated sensorimotor integration may be a useful approach to reduce the risk of fall among elderly populations or when patients suffer from neurological deficits.